Clinical hepatotoxicity associated with antifungal agents. Issue 2 (1st February 2017) - Kyriakidis, Ioannis; Tragiannidis, Athanasios; Munchen, Silke; Groll, Andreas H.
ABSTRACT: Introduction : Invasive fungal diseases (IFDs) are a leading cause of morbidity and mortality among immunocompromised patients with bone marrow failure syndromes, hematological malignancies, hematopoietic stem cell transplantation (HSCT), those admitted in intensive care units (ICUs) and those with prolonged febrile neutropenia. IFDs occur in a setting of multiple morbidities and are associated with case fatality rates between 30 and 70%. Along with the development of classes and compounds, the last two decades have seen substantial improvements in the prevention and management of these infections and an overall increased use of antifungal agents. Areas covered : All antifungal agents, including amphotericin B formulations, echinocandins and the triazoles, may cause hepatic toxicity that ranges from mild and asymptomatic abnormalities in liver function tests to substantial liver injury and fulminant hepatic failure. Expert opinion : The present article reviews incidence and severity of hepatotoxicity associated with different classes and agents to provide a better understanding of this specific end organ toxicity and safer use of antifungal agents A thorough understanding of the distribution, metabolism, elimination and drug-drug interactions of antifungal agents used for management of IFDs in combination with safety data from clinical trials, pharmacokinetic and pharmacodynamic studies may guide the use of antifungal treatment in patients at high risk for the development of hepatic dysfunction and in those with underlying liver damage due to cytotoxic therapy.